Characterization of sepiapterin reductase activity from Drosophila melanogaster. - Ruiz-Vazquez, P.; Silva, F.J.; Ferre, J. (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 1996)
A kinetic study of Drosophila melanogaster sepiapterin reductase has been done. The apparent Km for sepiapterin has been estimated as 153 microM. N-acetyldopamine, N-acetylserotonin, and N-methoxyacetylserotonin have shown to be noncompetitive inhibitors for the Drosophila sepiapterin reductase. The Ki obtained were 40 microM, 127 microM and 87 microM, respectively. Chromatofocusing of Drosophila crude extracts has shown only one peak with sepiapterin reductase activity, corresponding to pI 6.0. A study of the activity in different eye-color mutant strains revealed significantly decreased levels in clot, red Malpighian tubules and garnet.